Education governance and standardised tests in Denmark and England. Issue 6 (2nd November 2018) - Kelly, Peter; Andreasen, Karen Egedal; Kousholt, Kristine; McNess, Elizabeth; Ydesen, Christian
Abstract: In this study we identify and compare the impact of standardised student assessment in England, an established neoliberal context, and in Denmark where a neoliberal education reform agenda is emerging in response to both national concerns and international governance. National reading tests for students aged 11–12 years, long established in England, were introduced in Denmark in 2010. The form they take differs considerably, being primarily formative in Denmark and largely summative in England. Culturally sensitive extended semi-structured interviews are conducted with both teachers and students and analysed to identify the extent to which neoliberal reform is mobilised through testing in each context and how testing shapes curriculum and pedagogy. Significantly, we find that in Denmark, where professional judgement still dominates, teachers often deploy pedagogical approaches to service what they believe to be their students' best interests. In England, however, teachers try to accommodate a concern for both their students' and their own interests, and the pedagogy they enact is more often controlling, instrumental and reductionist; their wish to be proactive is compromised by their need to be responsive. Hence we show how policy technologies shape practice to undermine a deliberate pedagogy rooted in ideas legitimated though scholarship and experience.